PENYULUHAN PEMBERANTASAN SARANG NYAMUK DI POSYANDU ANGSANA WAY HALIM PERMAI TAHUN 2017 - Usastiawaty Cik Ayu Saadiah Isnainy; Teguh Pribadi; Lidya Ariyanti; Dewi Novalina (JURNAL KREATIVITAS PENGABDIAN KEPADA MASYARAKAT (PKM), 2018)
ABSTRACT Prevention of mosquito population was done by eradication of mosquito larvae, mosquito eggs, and mosquitoes in various ways. The larvae are targeted in controlling that act as vector-borne diseases through mosquitoes, such as malaria and dengue hemorrhagic fever. The purpose of the activity is expected to understand how to eradicate mosquito breeding. This activity was done on Thursday, December 14, 2017. The activity consist of education to the residents on how to eradicate mosquito breeding in the work area of Way Halim health center, using LCD and leaflets. There was a significant result of people knowledge after education. Thus, the provision of education can provide increased knowledge, especially with regard to eradicating mosquito breeding. Keywords: Mosquito, Larva, Eradication